2006
DOI: 10.1016/j.icesjms.2006.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Otolith shape and temporal stability of spawning groups of Icelandic cod (Gadus morhua L.)

Abstract: G. 2006. Otolith shape and temporal stability of spawning groups of Icelandic cod (Gadus morhua L.). e ICES Journal of Marine Science, 63: 1501e1512.During the past 5e10 years, studies exploring small-scale structure of cod populations have provided accumulating evidence for the existence of local populations. In Iceland, all cod have been thought to belong to a single management unit. Recent studies on genetic and life history variation have, however, indicated the existence of local populations. The main obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 40 publications
6
47
0
3
Order By: Relevance
“…Previous studies have found differences in genetic structure (Pampoulie et al 2006), otolith morphology (Jónsdóttir et al 2006b;Petursdóttir et al 2006) and microchemistry (Jóns-dóttir et al 2006a), and growth and maturity (Jónsdóttir et al, 2008;Marteinsdóttir and Begg, 2002) between the two groups. Our results indicate that physiologically, northern and southern Iceland cod perform differently when reared in a common environment and exposed to the same experimental conditions and suggests a genetic basis for these differences (Reznick 1982;Imsland and Jónsdóttir 2002;Roff 2002;Roff 2002;Conover et al 2006;Hutchings et al 2007).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have found differences in genetic structure (Pampoulie et al 2006), otolith morphology (Jónsdóttir et al 2006b;Petursdóttir et al 2006) and microchemistry (Jóns-dóttir et al 2006a), and growth and maturity (Jónsdóttir et al, 2008;Marteinsdóttir and Begg, 2002) between the two groups. Our results indicate that physiologically, northern and southern Iceland cod perform differently when reared in a common environment and exposed to the same experimental conditions and suggests a genetic basis for these differences (Reznick 1982;Imsland and Jónsdóttir 2002;Roff 2002;Roff 2002;Conover et al 2006;Hutchings et al 2007).…”
Section: Discussionmentioning
confidence: 91%
“…Otolith shape analysis revealed low population differentiation and less than 50% classification accuracy. Shape analysis studies on deep-sea species have been relatively few compared to those of more coastal species (DeVries et al 2002;Jonsdottir et al 2006;Merigot et al 2007;Burke et al 2008;Hussy 2008). Those studies that have attempted to reveal stock structure in deep-sea species have been somewhat limited in their success (Stransky 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important to remember that the environmental conditions in the locations in which the cod, particularly those that were mature, were caught during the spring groundfish surveys were not necessarily those that had the most influence on their condition. With that in mind, evidence of structure in the Icelandic cod stock is accumulating; recent studies of otolith shape and chemistry and of genetic markers have detected differentiation between cod from the northeastern and southwestern regions and also with depth (Jónsdóttir et al 2006a,b, Pampoulie et al 2006, Pétursdóttir et al 2006. Spawning cod on the northeastern spawning grounds seldom migrate to the southwestern spawning areas and vice versa (Pampoulie et al 2006).…”
Section: (Continued)mentioning
confidence: 99%